CHARACTERISATION AND PRODUCTION OF POLY (LACTIC ACID)/POLY(ETHYLENE GLYCOL) MICROFIBER VIA MELT DRAWN SPINNING PROCESS - Mohd. Akhir , Nur Atiqah; Othman , Maizatulnisa; Buys, Yose Fachmi; Shaffiar, Norhashimah; Jimat, Dzun Noraini; Syed Shaharuddin, Sharifah Imihezri (IIUM Engineering Journal, 2020)
In this study, melt blended compositions of pure PLA with additions of polyethylene glycol (PEG) up to 30 wt% were prepared. Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimeter (DSC), and thermogravimetric analysis (TGA) were used to investigate the properties of PLA/PEG blends, such as structural, thermal, and morphological properties. The results showed that further increments of PEG cause the -OH group of PLA/PEG blends to show a broad peak, indicating that there is hydrogen bonding interaction between PEG and PLA chains. DSC result revealed that the addition of PEG decreases the glass transition temperature from 57 °C to 46 °C and crystallization temperature from 107 °C to 87 °C. Such trends suggest enhanced chain mobility of PLA chains. TGA thermograms showed that further additions of PEG into PLA resulted in a consistent shift to lower temperature and decrease in thermal stability. Optical microscopy (OM) and scanning electron microscopy (SEM) observations of the melt spun PLA/PEG microfibers revealed that the diameter of the microfibers averaged between 15 to 80 microns. ABSTRAK: Kajian ini menganalisa komposisi adunan lebur PLA asli bersama tambahan polietilena glikol (PEG) sebanyak 30%. Penjelmaan Fourier spektroskopi inframerah (FTIR), kalorimeter pengimbasan pembezaan (DSC) dan analisis termogravimetri (TGA) telah digunakan bagi mengkaji sifat-sifat adunan PLA/PEG, seperti struktur, terma dan sifat-sifat morfologi. Keputusan menunjukkan penambahan PEG seterusnya menyebabkan kumpulan -OH campuran PLA/PEG memberikan puncak yang lebar, ini menunjukkan ada interaksi ikatan hidrogen antara rantaian PEG dan PLA. Keputusan DSC menunjukkan penambahan PEG mengurangkan perubahan gelas dari 57 °C kepada 46 °C dan suhu kristalisasi dari 107 °C kepada 87 °C. Trend ini mencadangkan peningkatan pergerakan rangkaian pada rantaian PLA. Termogram TGA menunjukkan dengan penambahan berterusan PEG ke dalam PLA menghasilkan penurunan konsisten pada suhu dan pengurangan kestabilan haba. Pemerhatian mikroskop optik (OM) dan mikroskopi elektron penskanan (SEM) mikrofiber spun lebur PLA/PEG menunjukkan purata diameter mikrofiber ini antara 15 ke 80 mikron.